Registration of 'L 12‐201' sugarcane. Issue 2 (16th February 2022) - Pontif, Michael; Kimbeng, Collins; Gravois, Kenneth; Bischoff, Keith; Sexton, David; LaBorde, Christopher; Hawkins, Gertrude; Hoy, Jeffrey; Baisakh, Niranjan; Wilson, Blake; Orgeron, Albert; Todd, James; et al.
Abstract: 'L 12‐201' (Reg. no. CV‐206, PI 699125) sugarcane (an interspecific hybrid of Saccharum spp.) was released on 10 Apr. 2019 for commercial production in the Louisiana sugar industry. L 12‐201 was derived from a cross between the female parent 'L 97‐128' and the male parent 'HoCP 96‐540'. Early‐stage selection through the seedling and two unreplicated clonal stages by researchers at the Louisiana State University Agricultural Center culminated in the assignment of a permanent varietal designation in 2012. Thereafter, the experimental variety was further evaluated cooperatively with personnel from the USDA‐ARS at Houma and the American Sugar Cane League, Inc., at Thibodaux, LA, through several stages at multiple locations. In the final testing stage, data were collected from 60 replicated, combine‐harvested trials at 12 representative light‐ and heavy‐textured soil locations. Averaged across the plant‐cane crop, the sucrose content, cane yield, and sugar yield were significantly ( P  < .05) higher in L 12‐201 than in 'L 01‐299', the most widely grown cultivar in the Louisiana sugar industry. In the first‐ and second‐ratoon crops, L 12‐201 had significantly ( P  < .05) less cane yield and sugar yield than L 01‐299, but sucrose content was not significantly different between L 12‐201 and L 01‐299. When averaged across the light‐textured versus heavy‐textured soil locations, no significant differences in performance were found for L 12‐201 in any of the traits measured. The new cultivar had a lower stalk population and greater stalk weight compared with L 01‐299, especially in the ratoon crops. L 12‐201 is a mid‐maturing cultivar. Whenever possible, L 12‐201 should be harvested before the arrival of subfreezing temperatures because it is among the least cold tolerant cultivars in the industry. L 12‐201 is resistant to sorghum mosaic, smut, leaf scald, and ratoon stunt; moderately resistant to brown rust; and susceptible to yellow leaf and the sugarcane borer. Core Ideas: L 12‐201 sugarcane was released for cultivation in the Louisiana sugar industry. L 12‐201 was released because of its high yield potential compared with other cultivars. L 12‐201 is a mid‐maturing cultivar. Whenever possible, L 12‐201 should be harvested before the arrival of subfreezing temperatures.